2013
DOI: 10.1536/ihj.54.171
|View full text |Cite
|
Sign up to set email alerts
|

Interictal Electrocardiographic and Echocardiographic Changes in Patients With Generalized Tonic-Clonic Seizures

Abstract: Partial and generalized seizures often affect autonomic functions during seizures, and interictal and postictal periods. We investigated possible interictal electrocardiographic abnormalities in patients with generalized tonic-clonic seizures (GTCS), together with evaluating any structural heart changes by echocardiography in these patients in comparison with healthy controls. We studied 120 definite GTCS patients (76 males and 44 females) who are neither diabetic nor under any medical treatment, and 60 health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 36 publications
1
19
0
Order By: Relevance
“…According to previous surveys, the prevalence of arterial hypertension is similar in PwE as compared to the general population (84). This is in line with smaller scope studies reporting similar interictal BP values in people with FBTCS and healthy controls (85) as well as in individuals with epilepsy who later died of SUDEP and two matched control groups with and without epilepsy (86). The authors of the latter study found, however, that DAP tended to be higher in SUDEP patients, suggesting that the sympathetic tone is elevated in this patient group (86).…”
Section: Interictal Alterations Of Blood Pressure and Baroreflex In Esupporting
confidence: 89%
“…According to previous surveys, the prevalence of arterial hypertension is similar in PwE as compared to the general population (84). This is in line with smaller scope studies reporting similar interictal BP values in people with FBTCS and healthy controls (85) as well as in individuals with epilepsy who later died of SUDEP and two matched control groups with and without epilepsy (86). The authors of the latter study found, however, that DAP tended to be higher in SUDEP patients, suggesting that the sympathetic tone is elevated in this patient group (86).…”
Section: Interictal Alterations Of Blood Pressure and Baroreflex In Esupporting
confidence: 89%
“…Intermittent or permanent block of atrioventricular (AV) conduction or sinus node dysfunction are occasionally reported as side effects of sodium channel blockers . Interictal PR intervals as a measure of AV conduction have been reported to be shorter or longer in people with epilepsy as compared to controls, but conclusive data on larger study populations are lacking. Periictal bradycardia and asystole are well‐known phenomena and can occur in up to one third of individuals (but only in a small fraction of their seizures) with refractory epilepsy as assessed on long‐term ambulatory monitoring, whereas seizure‐related AV conduction blocks have been reported in some cases only .…”
Section: Risk Factors and Biomarkersmentioning
confidence: 99%
“…In most studies comparing people with epilepsy and without epilepsy, mild QTc prolongation was reported in those with epilepsy, 10–12 while others reported similar QTc durations in both groups, 13 14 or QTc shortening. 15 16 The number of people with severe QTc prolongation was not reported in these studies.…”
Section: Introductionmentioning
confidence: 96%